If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -83 = 2v + -15v + -18 Reorder the terms: -83 = -18 + 2v + -15v Combine like terms: 2v + -15v = -13v -83 = -18 + -13v Solving -83 = -18 + -13v Solving for variable 'v'. Move all terms containing v to the left, all other terms to the right. Add '13v' to each side of the equation. -83 + 13v = -18 + -13v + 13v Combine like terms: -13v + 13v = 0 -83 + 13v = -18 + 0 -83 + 13v = -18 Add '83' to each side of the equation. -83 + 83 + 13v = -18 + 83 Combine like terms: -83 + 83 = 0 0 + 13v = -18 + 83 13v = -18 + 83 Combine like terms: -18 + 83 = 65 13v = 65 Divide each side by '13'. v = 5 Simplifying v = 5
| x+x+6x=119+6x | | 6x+8=-4x | | 3x=-2x-5 | | 5x+15/5=35-x | | 6x+8=11-4x | | 2x^3-5x=27 | | 4*x+43+2*x=7 | | (0.3+2x)(0.5+2x)=5.3018 | | -9*x-2*x-18=26 | | 108+(5x+8)=x | | -(9-3a)-(4+2a)-3=-(2-5a)+(-a)+1 | | x/2+x/4+x/5=x-1 | | w*5-7+w*2=-17 | | 3*3=8 | | 48-54+30= | | 63x^2-24x-15=0 | | -9(9-3a)-(4+2a)-3=-(2-5a)+(-a)+1 | | q^2+4q+4=26 | | 6-+4=210 | | 3x+20=5-16 | | (3x-4)(x-3x+2)= | | x/30=9 | | 16=s-p | | 12v^2+12v-15=0 | | 72-4.9t^2=8t | | 4x-4=-48 | | 3/10+7/10 | | 0-600*2-600*2+X*2-0.2X*4=0 | | a^2-a-8=0 | | 7/10+1/5 | | 4x+7-3x=15 | | -4n+2+3n=8-n+6 |